ONLINE LENDING IN THE DIGITAL ERA IN THE PERSPECTIVE OF ISLAMIC ECONOMIC LAW - Safitri, Gieni Devi; Masruroh, Nikamatul; Munir, Misbahul (Universitas Islam Negeri Mataram, 2023)
The increasingly developing technology era makes the internet one of the dependencies in everyday life. The emergence of online loan services has an impact on people's economic life. Online loans have easy access and are not complicated to apply for business capital. However, many people still do not understand Sharia economic law in online lending services; therefore, the author aims to analyze online loans in the digital era from an economic law perspective. This research method uses descriptive qualitative analysis. The study results found that judging from online loans, it is permissible in case that there are no elements of usury, gharar, maysir, tadlis, dharar, zulm, and haram.